2017
DOI: 10.2109/jcersj2.16274
|View full text |Cite
|
Sign up to set email alerts
|

High durability of La<sub>0.6</sub>Sr<sub>0.4</sub>Co<sub>0.2</sub>Fe<sub>0.8</sub>O<sub>3&minus;&delta;</sub>/samaria-doped ceria (SDC) composite oxygen electrode with SDC interlayer for reversible solid oxide fuel cell/solid oxide electrolysis cell

Abstract: We have examined the long-term durability of a La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3¹¤ (LSCF)samaria-doped ceria (SDC) composite oxygen electrode with SDC interlayer for reversible solid oxide cells (R-SOCs). A symmetrical cell with the configuration: LSCF SDC«SDC interlayer«yttria-stabilized zirconia (YSZ) electrolyte«SDC interlayer«LSCFSDC, was operated at 900°C and a constant current density of 0.5 A cm ¹2 with the top electrode as the anode (O 2 evolution). The IR-free overpotentials at both the anode and cathod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…To clarify the effects of polarization current direction on the activity of LSC-based electrodes, Shimura et al [152] studied symmetric LSCF-SDC composite electrodes on YSZ electrolytes with dense SDC barrier layers under polarization at 900 °C and 0.5 A cm −2 for 5500 h. Here, these researchers reported that the overpotentials under anodic and cathodic modes remained constant over the operational duration in which the cell ohmic resistance increased from 0.5 to 0.8 Ω cm 2 after cathodic polarization, whereas the increase after anodic polarization was very small. Elemental analysis further showed significant Sr accumulation at the YSZ/SDC interlayer interface after cathodic polarization, which was consistent with cell ohmic resistance increases under cathodic polarization.…”
Section: Reversible Polarizationmentioning
confidence: 99%
“…To clarify the effects of polarization current direction on the activity of LSC-based electrodes, Shimura et al [152] studied symmetric LSCF-SDC composite electrodes on YSZ electrolytes with dense SDC barrier layers under polarization at 900 °C and 0.5 A cm −2 for 5500 h. Here, these researchers reported that the overpotentials under anodic and cathodic modes remained constant over the operational duration in which the cell ohmic resistance increased from 0.5 to 0.8 Ω cm 2 after cathodic polarization, whereas the increase after anodic polarization was very small. Elemental analysis further showed significant Sr accumulation at the YSZ/SDC interlayer interface after cathodic polarization, which was consistent with cell ohmic resistance increases under cathodic polarization.…”
Section: Reversible Polarizationmentioning
confidence: 99%
“…1 μm). 16,17 An air reference electrode (ARE) was prepared by wrapping a Pt wire around the periphery of the YSZ electrolyte disk with Pt paste.…”
Section: Methodsmentioning
confidence: 99%
“…8,12,13 The degradation mechanism of the oxygen electrodes observed in both operation modes has been clarified, i.e., unfavorable solid-state reactions between the perovskite-oxides and the YSZ electrolyte through interlayer defects (or grain boundaries) and electrode delamination. [13][14][15][16][17] In contrast, the mechanism for the degradation of the Ni-YSZ cermet electrode for the hydrogen evolution reaction (HER) in the SOEC mode has remained unclear. 14,15,18,19 For Ni-YSZ cermet electrodes, a depletion of Ni close to the electrode/YSZ electrolyte interface has been reported, specifically, at high current densities (or high overpotentials), in addition to segregation of impurities (such as Si) at the triple phase boundary (TPB) and/or agglomeration of Ni.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The set-up for the test cell was described in Shimura and coworkers report [44]. The test cell was sealed with a gold ring.…”
Section: Electrochemical Measurementmentioning
confidence: 99%